University Learners’ Motivation and Experiences in Using Virtual Laboratories in a Physics Course - Afacan Adanır, Gülgün; Akmatbekova, Azat; Muhametjanova, Gulshat (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2022)
It is becoming necessary to examine learners’ use of and experiences with virtual laboratories. Learners’ interest and motivation to use virtual laboratories are important factors for the success of these platforms. This study was conducted to analyze Kyrgyz learners’ use of virtual laboratories in a physics course at the university level. The study was performed in the 2019–2020 spring term at a state university in Kyrgyzstan. The study took a quantitative approach, with 376 Kyrgyz learner participants studying at the undergraduate level. The participants were divided into three groups: the first and second used different virtual laboratory platforms, while the third was involved in face-to-face labs. Quantitative data were collected using an online questionnaire which consisted of items related to demographic characteristics, motivation and experience, and physics laboratory attitudes. The results demonstrated differences among the groups regarding factors of motivation and experience. In addition, learners’ physics laboratory attitudes differed with respect to gender and grade point average (GPA) factors.